PENGARUH PARTISIPASI PENDIDIKAN TERHADAP PERSENTASE PENDUDUK MISKIN - Dini Amaliah (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2015)
Abstract: The aimofthis study was todetermine how muchInfluence ofthe Gross EnrolmentRatio(GER) andnet enrollment ratio(NER) of thePercentage of Poor(Case Studies inJakartaInthe Year2009-2013). The research method is using a quantitative approach. Unitanalyzedwerethe percentageof poor people(PPM), the gross enrollment rate(GER) andnet enrollmentratio(NER). Source of dataissecondary datain the form ofbooks, dictionaries, scientificarticles, data collectedandpublishedbythe Central Bureauof Statistics(BPS). Hypothesistestingconcluded thatthere was nosignificanteffect ofGERandenrollment atthe percentageofpoor peopleinJakarta in2009-2013eitherpartially orjointlyrepresented bythe magnitudeof0.572calculated F<F table9.55on the level0.05significant.Keywords: gross enrollment ratios, enrollment at, Percentage of Poor People